Foundations of augmented cognition. directing the future of adaptive systems 6th International Conference, FAC 2011, Held as Part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011. Proceedings - Schmorrow, Dylan D.; Fidopiastis, Cali M. (LNCS sublibrary. SL 7, Artificial intelligence, 2011)
This book constitutes the refereed proceedings of the 6th International Conference on Augmented Cognition, FAC 2011, held in Orlando, FL, USA in July 2011, within the framework of the 14th International Conference on Human-Computer Interaction, HCII 2011, with 11 other thematically similar conferences. The 75 full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical parts on theories, models, and technologies for augmented cognition; neuroscience and brain monitoring; augmented cognition, social computing, and collaboration; augmented cognition for learning; augmented cognition and interaction; and augmented cognition in complex environments.